Adsorption of a Non-Ionic Surfactant on Soils: A Model Study - Xiaobo Xue; Yanmei Zhou; Dongshen Wang (Adsorption Science & Technology)
The adsorption of the widely used non-ionic surfactant Triton X-100 (TX) onto three model inorganic soil components (silica powder, γ-alumina and calcite) was investigated in a series of batch experiments in which the aqueous phase was equilibrated with the solid under different solution conditions. TX showed no discernable adsorption onto γ-alumina over the pH range 3.8 < pH < 12.1 and a temperature of 15°C or onto calcite at the same temperature and pH range 7.7 < pH < 11.7. However, significant and reversible adsorption from solutions was found for silica powder suspensions. The adsorption isotherms obtained for TX uptake onto silica powder were best fitted by the Freundlich model. An increase in the ionic strength of the electrolytic solution led to a decrease in the surface concentration of TX on silica powder, indicating significant electrostatic interactions between TX and silica powder particles, possibly through interaction with the surface silanol groups of the solid substrate. Increasing the pH value of the electrolyte solution from 6 to 9 led to a considerably decrease in the amount of TX adsorbed, while a decrease in the solution pH from 6 to 3 had only a slight effect on the surface concentration of adsorbed TX. The adsorption of TX onto silica powder decreased as the temperature was increased in the range 15–45°C, indicating that the adsorption process was exothermic. The magnitude of the calculated enthalpy of adsorption (ca. 10 kJ/mol) demonstrated that the uptake at the solid/liquid interface at an equilibrium pH of 6.1 was largely due to physisorption.